Konten Instagram @infosikka sebagai Media Informasi Publik Kabupaten Sikka - Sino, Maria Lelo; Gobang, Jonas K.G.D.; Sedu, Viktor Ariestyan; Kedoh, Lodowik N (UMSU, 2025)
ABSTRACT The field of managing public opinion and aspiratios, Sikka Diskominfo uses instagram as a public information medium for Sikka district. With instagram, Diskominfo Sikka should be able to facilitate communication between the government and the public. However, in practice the communication that occurs is less effective on the @InfoSikka account. This research aims to find out of the reasons why Diskominfo Sikka uses instagram as a means of disseminating information and secondly how the field of managing public opinion and aspiratios manages instagram conten as a public news. This research is qualitative research with the consept of a public relations model. This research approach is descriptive analysis, post positivm paradigm, and case study method. The result of this research show that Diskominfo Sikka chose instagram as as a public information because of the large number of application users, as well as the convenience, speed and visual features it offers. Diskominfo Sikka spreads News in the form of press release content, although few people respond, Diskominfo Sikka continues to consistenly produce news every day so that there is always information about Sikka district. Keywords: Instagram, Media Information, Sikka Regency